TANAH HUTAN KOTA YANG MENJADI WISATA KULINER DI BEKASI - Claudia Eleonora Marshinta; Meta Indah Budhianti (Reformasi Hukum Trisakti, 2022)
In place of the urban forest land, which should be 90% to 100% trees and green space, culinary tours are constructed. The issue is whether the culinary tourism facility constructed on urban forest land in Bekasi complies with regional regulations for the city of Bekasi. If not, what legal actions can the regional government of the city of Bekasi take to ensure that the required percentage of green open spaces is met? The research methodology is normative and descriptive in nature, with secondary data sources, interviews and literature reviews used for data collecting, qualitative approaches for data analysis, and deductive reasoning used for drawing findings. The study's findings, followed by a discussion and conclusion that culinary tours may be developed provided they get approval from the Bekasi city authority. The regional rule of the city of Bekasi number 5 of 2016 states this. The city government is attempting to convert vacant and abandoned land into a green zone in order to meet the Bekasi proportion. Spatial planning has been incorporated into regional legislation as part of this effort.